2021
DOI: 10.47717/turkjsurg.2021.5157
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of laparoscopic percutaneous internal ring suturing method and open inguinal hernia repair in children under 3 months of age

Abstract: Objective: Laparoscopic inguinal hernia repair in younger infants has not been completely accepted worldwide. The aim of this study was to evaluate the safety and feasiblity of laparoscopic percutaneous internal ring suturing method in children aged younger than 3 months and compare the recurrence and complication rates with open repair; which may still be mentioned as the gold standard procedure. Material and Methods: A total of 387 children underwent inguinal hernia repair in the clinic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…When we compare the findings of our current study of neonates with our previous study of children >1 year old [5], our surgical times appear to be higher in neonates (20.3 vs 14.3 for unilateral and 25.8 vs 20.4 for bilateral repair.) On the other hand, in a study of children <3 months of age undergoing PIRS [12], the mean surgical time of 85 children was reported as 24 minutes for unilateral and 33 minutes for bilateral PIRS, similar to our findings. Patkowski et al also reported their experience with PIRS in children <3 months of age, with an average surgical time of 23 minutes for unilateral and 26 minutes for bilateral hernias [11].…”
Section: Discussionsupporting
confidence: 91%
“…When we compare the findings of our current study of neonates with our previous study of children >1 year old [5], our surgical times appear to be higher in neonates (20.3 vs 14.3 for unilateral and 25.8 vs 20.4 for bilateral repair.) On the other hand, in a study of children <3 months of age undergoing PIRS [12], the mean surgical time of 85 children was reported as 24 minutes for unilateral and 33 minutes for bilateral PIRS, similar to our findings. Patkowski et al also reported their experience with PIRS in children <3 months of age, with an average surgical time of 23 minutes for unilateral and 26 minutes for bilateral hernias [11].…”
Section: Discussionsupporting
confidence: 91%
“…This finding was a bit similar to a study conducted by Kumar and colleagues 9 which showed that incidence of occult hernia was 16.67%. Safety of laparoscopic single port herniotomy with respect to recurrence, wound infection and cosmetics has also been mentioned by Ergun et al 17 . Recurrence rate in our research was 3.57% (1/28) while Zenitani et al 18 reported similar results in their series of 120 patients with regard to safety and efficacy in children and a lower rate of metachronous contralateral inguinal hernia.…”
Section: Discussionmentioning
confidence: 82%
“…However, the learning curve of TUSLIC may be long and steep, which requires much simulator training, even for a senior surgeon. Therefore, this may explain why the ORT in patients receiving TUSLIC was much longer than that of patients receiving TAMLEC or PIRS (20,(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%